2006
DOI: 10.5840/beq200616223
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sector Alliance Learning and Effectiveness of Voluntary Codes of Corporate Social Responsibility

Abstract: Firms and industries increasingly subscribe to voluntary codes of conduct. These self-regulatory governance systems can be effective in establishing a more sustainable and inclusive global economy. However, these codes can also be largely symbolic, reactive measures to quell public criticism. Cross-sector alliances (between for-profit and nonprofit actors) present a learning platform for infusing participants with greater incentives to be socially responsible. They can provide multinationals new capabilities t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 68 publications
1
114
1
3
Order By: Relevance
“…For example, Esbenshade (2001) argues that adopting codes of conduct provides a way for corporations both to prevent the enforcement of existing labour laws and forestall future legal reforms. Similar claims are readily found in previous research (e.g., Diller, 1999;Bondy et al, 2004;Royle, 2005;Arya and Salk, 2006), and, as Bartley (2005, p. 212) points out, a common argument is that " one unfortunate effect of the rise of private regulation will be to displace or 'crowd out' public regulation and legal accountability" .…”
Section: Plausible Motives For Adopting International Framework Agreesupporting
confidence: 63%
“…For example, Esbenshade (2001) argues that adopting codes of conduct provides a way for corporations both to prevent the enforcement of existing labour laws and forestall future legal reforms. Similar claims are readily found in previous research (e.g., Diller, 1999;Bondy et al, 2004;Royle, 2005;Arya and Salk, 2006), and, as Bartley (2005, p. 212) points out, a common argument is that " one unfortunate effect of the rise of private regulation will be to displace or 'crowd out' public regulation and legal accountability" .…”
Section: Plausible Motives For Adopting International Framework Agreesupporting
confidence: 63%
“…This means that cross-alliance scholars (including SA) can learn much from literature related to strategic alliance (firm-firm) management. Although prior studies suggest that managers should adopt different management philosophies to deal with cross-sector collaboration (Arya and Salk 2006;Berger et al 2004;Rondinelli and London 2003;Selsky and Parker 2005), we challenge this claim. Instead, we postulate that some ideas regarding alliance management could be universal and may apply to the alliance relationship in different situations.…”
Section: Discussion and Conclusion Academic Contributioncontrasting
confidence: 48%
“…Furthermore, this finding also has wider implications regarding the learning opportunities for SENPOs on the issues relating to SA management. We introduced SA management routines by adopting the concept from firmfirm alliance management research (Arya and Salk 2006;Draulans et al 2003;Schilke 2014;Schilke and Goerzen 2010), and we confirmed its viability in the SA context. This finding also suggests that SENPOs can learn a great deal from the firm-firm alliance management literature.…”
Section: Managerial Implicationsmentioning
confidence: 82%
“…In recent years, several articles have pointed to the bridges that exist between BOP and subsistence markets scholars (e.g. Arya & Salk, 2006;Rivera-Santos et al, 2012).…”
Section: Discussionmentioning
confidence: 99%